Implementation of Teaching Practitioners In Improving The Quality of Learning and Implementing The Curriculum Merdeka Belajar - Fatma Tresno Ingtias; Dina Ampera; Farihah Farihah; Bakhrul Khoir Amal; Anwar Soleh Purba (Universitas Cokroaminoto Palopo, 2022)
This research departs from the problem of how the initial conditions of learning in the Department of Family Welfare Education (PKK), how to implement the collaborative learning model, how to implement the collaborative learning model through teaching practitioners in the Department of Family Welfare Education (PKK), and how it affectsthe improvement of the quality of learning and the implementation of the Merdeka Belajar Kampus Merdeka curriculum.The research methods used include (1) a Research and Depelopment approach to produce guidelines for the implementation of teaching practitioners in the Department of Family Welfare Education (PKK) and (2) a descriptive quantitative approach to determine the implementation of teaching practitioners in the Department of Family Welfare Education (PKK), toimprove the quality of learning and the Merdeka Belajar Kampus Merdeka curriculum (MBKM). The research respondents involved were lecturers in the Department of Family Welfare Education (PKK), Practitioners from the Industrial and Business World (DUDI), and Students. The results of the study are expected to produce Teaching Practitioner Guidelines in the Department of Family Welfare Education (PKK), because this guideline is very important as a standard operating procedure for the implementation of teaching practitioner activities on campus so as to be able to increase the partnership between the Department of Family Welfare Education (PKK), with DUDI and the successful implementation of the curriculum Merdeka Belajar Kampus Merdeka (MBKM). Meanwhile, the results of a descriptive quantitative analysis of the influence of teaching practitioners in the Department of Family Welfare Education (PKK), improving the quality of learning and developing the MBKM curriculum will provide recommendations in the formulation of policies for achieving IKU-4, namely teaching practitioners on campus